Multiyear evaluation of the agronomical and technological properties of a panel of spelt varieties under different cropping environments. (January 2023) - Hellin, Pierre; Escarnot, Emmanuelle; Mingeot, Dominique; Gofflot, Sebastien; Sinnaeve, Georges; Lateur, Marc; Godin, Bruno
Abstract: Spelt is an ancient cereal that is growing in popularity but the diversity present among the different varieties available makes it difficult to choose a variety for a specific use. A total 22 European spelt varieties were therefore evaluated during four years for their agronomical (e.g. yield and disease resistance) and technological (e.g. flour rheology and gluten quality) aptitudes, in two locations in Belgium following either conventional or organic farming practices. Significant differences were observed between varieties, years and environments for most measured variables. The multivariate analysis made it possible to define groups among the varieties meeting the expectations of the sector for the different commercial applications. Sérénité appeared as a good overall candidate, with an excellent combination of agronomical and technological traits. Older varieties and landraces generally yielded poorer agronomical and technological results. Overall, modern spelt varieties showed technological properties that are well suited for biscuit making. Baking properties of spelt varieties were shown to be closely related to the nature of their high molecular weight glutenin alleles. The variety Zürcher Oberländer Rotkorn appeared as an outsider, with technological properties resembling those of bread wheat. Graphical abstract: Image 1 Highlights: Considerable agronomic and technological differences exist between spelt varieties. Both the growing season and the cropping environment impact spelt properties. Zürcher Oberländer Rotkorn has atypical technological properties for spelt. Spelt varieties could be clustered in 3 agronomic and 5 technological groups. The grouping facilitates the selection of spelt varieties for targeted applications.